A mechanistic thermal balance model of dairy cattle. (September 2021) - Li, Jinghui; Narayanan, Vinod; Kebreab, Ermias; Dikmen, Serdal; Fadel, James G.
Abstract : A dynamic model describing the thermal balance of Holstein dairy cattle was developed. The model quantified the heat flow of five main nodes at the body core, top and bottom skin, and top and bottom coat of a dairy cow. Heat production by the animal and heat flows between the animal and the environment, including conduction, convection, evaporation and radiation, were calculated based on existing models and physical principles. The model requires information of climate, animal characteristics and location as inputs, and returns body core, skin and coat temperatures as outputs. The thermal balance model was evaluated through two datasets. The root mean squared error of prediction for body temperature was 1.16 °C and 0.40 °C for the two datasets, respectively. A simulation study was conducted based on a Holstein dairy cow with 600 kg of body weight and 25 kg of daily milk yield under a typical summer environment in California, USA for three days. The average simulated temperatures of body, top and bottom skin, and top and bottom coat were 40.9, 35.6, 35.9, 34.1 and 33.7 °C, respectively. A local and a global sensitivity analyses showed that heat production, surface area and the parameters relative to respiration and sweating were the most sensitive. The model is able to predict the dynamic change of body temperature under hot weather, and to guide the use of physical cooling strategies, such as shade, fans, sprinklers and cooling mats in dairy facilities. Highlights: Dynamic model describing the thermal balance of Holstein dairy cattle was developed. Model predicts dynamic change of body temperature and heat transfer under hot weather. Thermal balance model evaluated with two datasets using sensitivity analysis. Heat production, surface area and respiration/sweating most sensitive parameters.